Communism in Germany under the Weimar Republic. - Fowkes, Ben (London : Macmillan Press, 1984)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: Kommunistische Partei Deutschlands (KPD).; communisme; Duitsland